Organizational Commitment As A Mediating Variable Of The Influence Of Organizational Climate On Employee Performance - Julindrastuti, Dijah; Karyadi, Iman (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
Organization is one of the places needed by an employee to develop their skills and also as a place to meet needs. In running its operations, the existence of an employee is one of the factors that greatly determines the success of an organization. An organization that is able to provide a good work climate and has a good commitment will be able to bring comfort in working so that it will have a good influence on employee performance. Good employee performance will have a positive impact on the success of the organization. Creating a sense of comfort in working can be done in various ways, including by paying attention to employee needs, appreciating employees, establishing good cooperation with employees. In addition to a sense of comfort or also called a good organizational climate, there is a good commitment in running the company. Good organizational commitment will also make employees work well because they have confidence and trust in the company. Researchers are interested in conducting research entitled